PTU-068 Patient Awareness of Immunisation Guidelines in Inflammatory Bowel Disease. (4th June 2013) - Amir, K; Chan, D; Kang, J-Y; Pollok, R; Neild, P; Poullis, A
Abstract : Introduction: Immunomodulator agents are commonly employed in the management of inflammatory bowel disease (IBD). These can increase the risk for opportunistic infections. This study aims to assess patient awareness for the need for appropriate immunisations, as outlined in published guidelines by the European Crohn's and Colitis Organisation (ECCO) [1]. Methods: Over a four-month period, IBD patients attending the Gastroenterology Departments' of St. George's Hospital and Queen Mary's Hospital were identified. Convenience sampling was used; all IBD patients encountered in these clinics were asked to participate. Patients were asked to complete a questionnaire, gathering information about their disease and immunisation awareness. Results: 135 patients participated in the study. 73 patients were male. Mean age was 43 years (with the range being 19–82 years). 53 patients had ulcerative colitis, 73 had crohn's disease and 9 were unsure of their diagnosis. Mean time since diagnosis was 8 years. 18 patients (13.3%) were currently receiving no drug therapy. 34 (25.1%) were being treated with immunomodulator agents (azathioprine, 6-mercaptopurine, methotrexate or cyclosporin). 4 patients (2.9%) were solely receiving biologics (infliximab or adalimumab), and 46 patients (34.0%) were on 5-aminosalicylic acids (5-ASAs) only. 27 patients (20%) were on a combination of thiopurines and 5-ASA therapy, and 6 patients (4.4%) were on a combination of infliximab, azathioprine and 5-ASA. Prednisolone therapy had been taken at some stage of treatment by 72 patients (53.3%). The majority of patients were not aware if they had been screened at diagnosis for the specific infections outlined by ECCO. Of the total 135 patients the following were aware that they had undergone screening: 4 (2.9%) for varicella zoster virus (VSV), 1 (1.9%) for hepatitis B virus (HBV), 3 (2.2%) for human immunodeficiency virus (HIV), 2 (1.4%) for hepatitis C virus (HCV) and 15 (11.1%) for tuberculosis (TB). Of the 135 patients: 4 (2.9%) recalled been offered immunisation against VZV, 16 (11.8%) against HBV, 51 (37.7%) against influenza, 33 (24.4%) against pneumococcus and none against human papilloma virus. 98 (72%) patients had not had any discussions with their General Practitioner about immunisations, 45 (33%) had read the immunisation advice distributed to all IBD patients from clinic. Conclusion: Our findings show that IBD patients are largely unaware of recommendations by ECCO regarding immunisation. Patient awareness needs to be increased regarding opportunistic infections and prevention with immunisations. A patient awareness campaign to educate IBD patients has been started in our clinics. Disclosure of Interest: None Declared Reference: European Crohn's and Colitis Organisation (ECCO) guidelines (2009). http://www.ecco-ibd.tv/index.php/publications/ecco-guidelines